Designing and Implementing a Project Based Learning Oriented English Syllabus to Help Eighth Graders Improve Their Communicative Skills at a Public School in Medellín (2017)
ABSTRACT: This action research explores to what extent the implementation of a contextualized syllabus designed by my cooperating teacher and me can help eighth graders improve their communicative skills at a public school in Medellín through the use of Project Based Learning. This implementation took into consideration the fact that motivation is a must to learn an additional language, so students need to find a real purpose for learning English. Thus, after having asked students what they would like to do in the English class, we decided together that they would create a simple short video clip of a story in groups. Data collection of this project included interviews, surveys, journals, and students’ artifacts, which were developed at the beginning, the middle and the end of the implementation. Preliminary findings have shown that, to some extent, students improved their communicative skills, such as retelling a simple story, expressing simple ideas without using a translator, and being more confident at speaking English. However, due to lack of time, the large number of students, some classroom management issues, and students’ lack of commitment, students had some difficulties working in groups, and the project was not as meaningful as expected.